2005
DOI: 10.1158/0008-5472.can-04-3161
|View full text |Cite
|
Sign up to set email alerts
|

Immortal DNA Strand Cosegregation Requires p53/IMPDH–Dependent Asymmetric Self-renewal Associated with Adult Stem Cells

Abstract: Because they are long-lived and cycle continuously, adult stem cells (ASCs) are predicted as the most common precursor for cancers in adult mammalian tissues. Two unique attributes have been proposed to restrict the carcinogenic potential of ASCs. These are asymmetric self-renewal that limits their number and immortal DNA strand cosegregation that limits their accumulation of mutations due to DNA replication errors. Until recently, the molecular basis and regulation of these important ASC-specific functions we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
104
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(116 citation statements)
references
References 32 publications
9
104
0
3
Order By: Relevance
“…However, increased self-renewal alone cannot account for SC expansion, if the modality of SC division remains prevalently asymmetric. Interestingly, it has been shown that p53 controls the modality of cell division in both mouse and human fibroblasts, as well as in adult mammary epithelial cells, and this function might also take place in adult SCs [70][71][72]. Indeed, we have recently demonstrated [34] in vitro that p53 loss allows mammary SC symmetric divisions and that this fact correlates in vivo with amplification of the mammary SC pool and geometric expansion of SCs during the life of p53 null mice.…”
Section: Discussionmentioning
confidence: 76%
“…However, increased self-renewal alone cannot account for SC expansion, if the modality of SC division remains prevalently asymmetric. Interestingly, it has been shown that p53 controls the modality of cell division in both mouse and human fibroblasts, as well as in adult mammary epithelial cells, and this function might also take place in adult SCs [70][71][72]. Indeed, we have recently demonstrated [34] in vitro that p53 loss allows mammary SC symmetric divisions and that this fact correlates in vivo with amplification of the mammary SC pool and geometric expansion of SCs during the life of p53 null mice.…”
Section: Discussionmentioning
confidence: 76%
“…An alternative epigenetic explanation for asymmetrical cell division has been proffered, termed the 'silent sister hypothesis', proposing that the daughter cell remaining as a stem cell selectively retains chromatids with active stem cell genes, with loss of stem cell properties in the cell that inherits the opposite 'silent' sister chromatids [13]. In studying embryonic fibroblasts in vitro, immortal strand co-segregation has been found to require both p53 and down-regulation of inosine monophosphate dehydrogenase (IMPDH), the rate-limiting enzyme for guanine nucleotide biosynthesis [14]. Not all studies concur with the hypothesis; haematopoietic stem cells (HSCs) with long-term repopulating activity have certainly been shown not to retain older DNA strands during division [5].…”
Section: Selective Dna Strand Segregationmentioning
confidence: 99%
“…DNA damage can activate ataxia telangiectasia mutated (ATM), a serine/threonine kinase, which can phosphorylate Chk2 and destabilize MDM2, an E3 ubiquitin ligase that negatively regulates the p53 stability. 22 To determine whether the induction of p53 in the L-Atg5-KO mouse liver was due to the ATM signaling pathway activated by DNA damage, we analyzed the expression of ATM, Chk2 and MDM2 in the liver tissues of L-Atg5-KO mice. As shown in Figure 6a, there was an apparent increase of total ATM and phosphorylated ATM in both non-tumor and tumor liver tissues of L-Atg5-KO mice.…”
mentioning
confidence: 99%